ХҚТУ-нің БОТАНИКАЛЫҚ БАҒЫНДАҒЫ ЗИЯНКЕСТЕР ТҮРЛЕРІ ЖӘНЕ ОЛАРМЕН КҮРЕСУ ЖОЛДАРЫ (Experimental biology, 2011)
This article deals with the problems of distribution of wreckers-insects decoraniv and fruit introducents of A. Yassawi International Kazakh-Turkish University and measures of struggle against them
Keywords: wreckers-insects; fruit introducents